2006
DOI: 10.1248/bpb.29.2359
|View full text |Cite
|
Sign up to set email alerts
|

Ochnaflavone, Naturally Occurring Biflavonoid, Inhibits Phospholipase A2 Dependent Phosphatidylethanolamine Degradation in a CCl4-Induced Rat Liver Microsome

Abstract: This study investigated the protective effects of a group IIA secretory phospholipase A 2 (sPLA 2 -IIA) inhibitor, ochnaflavone, on the progression of carbon tetrachloride (CCl 4 )-induced acute liver injury in rat liver microsomes in vitro. When rat liver was incubated at 37°C in the presence of CCl 4 , the level of phosphatidylethanolamine (PE) degradation increased markedly compared with the control. The rat 14 kDa platelet PLA 2 antibody, R377, suppressed the degradation of PE. Pretreating the microsome wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The increase in the PE contribution to total phospholipids suggested that Provinols treatment had a specific effect on phospholipid turnover because neutral lipids and fatty acid molecular species remain unchanged. Indeed, a reduction in PE degradation has been previously observed in platelets and liver microsomes due to inhibition of the secretory phospholipase A2 [42]. This result is suggestive of a reduction in the activity of phospholipase A2 in vessels from Provinols-treated rats especially when taken together with the reduction in the secretion of bioactive prostanoids.…”
Section: Discussionsupporting
confidence: 55%
“…The increase in the PE contribution to total phospholipids suggested that Provinols treatment had a specific effect on phospholipid turnover because neutral lipids and fatty acid molecular species remain unchanged. Indeed, a reduction in PE degradation has been previously observed in platelets and liver microsomes due to inhibition of the secretory phospholipase A2 [42]. This result is suggestive of a reduction in the activity of phospholipase A2 in vessels from Provinols-treated rats especially when taken together with the reduction in the secretion of bioactive prostanoids.…”
Section: Discussionsupporting
confidence: 55%
“…There are various phospholipases (PLA1, PLA2, PLC and PLD) that exhibit substrate specificities for different positions in phospholipids. Phospholipase A2 (PLA2) hydrolyzes the sn-2 ester bond in PC/PE, forming arachidonic acid and lyso-PC/lyso-PE [ 17 19 ]. These bioactive lipid mediators play important roles in inflammation, phospholipid metabolism, and signal transduction, which participate in the progression of DILI.…”
Section: Discussionmentioning
confidence: 99%
“…Two apigenin units are linked via an etheric linkage bond (Figure ). OC has been reported to possess many effective bioactivities for diverse diseases as described in precedent literatures . Naturally occurring biflavonoids as well as unnatural synthetic biflavonoids exhibited promising anti‐inflammatory activity through multiple mechanisms .…”
Section: Inhibition Of Pge2 and No Production By 7 12 Ochnaflavonementioning
confidence: 98%